Synthesis of some novel azo derivatives of 3,5-dimethly-1-(2-hydroxyethyl)pyrazole as potent analgesic agents - KAYMAKÇIOĞLU, BEDİA; KABASAKAL, LEVENT (WILEY-V C H VERLAG GMBH, 2006)
A series of 1-(2-hydroxyethyl)-3,5-dimethylpyrazolylazo derivatives, incorporating thiosemicarbazide 2a-c, 1,3,4-thiadiazole 3a-c, and 1,2,4-triazole-3-thione 4a-c were synthesized. The structure of these novel synthesized compounds 2a-c, 3a-c, and 4a-c was confirmed by spectral analysis. All these compounds were screened for their analgesic activity. Hot-plate and tail-immersion tests were used for the determination of the analgesic activity. Morphine, an analgesic through both spinal and supraspinal pathways, was used as a standard test drug. All compounds were administered at a dose of 100 mg/kg i.p. Among the compounds, 2-(butylamino)-5-[((1-(2-hydroxyethyl)-3,5-dimethylpyrazole-4-yl)azo)phenyl]-1,3,4-thiadiazole 3a and 4-[((1-(2-hydroxyethyl)-3,5dimethylpyrazole-4-yl)azo)phenyl]-4-(2-phenethyl)-2,4-dihydro-3H-1,2,4-triazole-3-thione 4c showed analgesic effects in both tests. Especially 4c exerted strong analgesia starting at 30 min after injection.
Keywords: phenylazo compounds; pyrazoles; thiadiazoles; triazoles; analgesic activity; ANTICONVULSANT ACTIVITY; BIOLOGICAL EVALUATION; ANTITUBERCULOSIS ACTIVITY; 1,3,4-THIADIAZOLE; 1,2,4-TRIAZOLE; ANALOGS; INDOLE; RATS; MICE